Assertive behavior and emotions and feelings management in university teachers formation - Acevedo Tovar, Luz Marina (2014)
We consider that the docent profile is mainly determinedby the type of education given in schools; therefore the docent will determine what kind of human (student) we make. Thus our interest is to know the level of development in social skills in students that intend to become teachersin the Education Faculty of the Universidad Nacional Mayor de San Marcos.Our work is to analyze the teacher, the docent in formation.Our goal is to determine the development level in social skills: assertive communication and emotions and feelings management in the students involved in this investigation.The investigation is comparative-descriptive and the designis transversal therefore it describes and compares thelevel of development in social skills in students of the 2nd and 10th cycle, this means two moments: to begin and tofinalize university studies.The instruments applied consisted in an “Affective selfknowledge test” and a poll designed especially for this investigation. Finally we established that there is no significative difference in the social skills development level in studentsof the 2º and 10º cycle.